Drivers of Spatiotemporal Variation in Survival in a Flyway Population: A Multi-Colony Study - Tjørnløv, Rune S.; Ens, Bruno J.; Öst, Markus; Jaatinen, Kim; Karell, Patrik; Larsson, Rolf; Christensen, Thomas Kjær; Frederiksen, Morten (Frontiers in Ecology and Evolution, 2020)
1. Spatio-temporal variation in population dynamics of migratory populations is shaped by exposure to different environments during the annual cycle. Hence, exposure to similar environments should translate into synchrony in vital rates. Despite a wide-ranging breeding population, the Baltic/Wadden Sea flyway population of eiders (Somateria m. mollissima) shares wintering grounds in the southern Baltic Sea, inner Danish waters and the Wadden Sea; different colonies within this flyway population are therefore likely to exhibit some degree of synchrony in vital rates. 2. Here we used capture-recapture-recovery data to investigate the impact of hunting, winter climate (the North-Atlantic Oscillation Index), winter temperature, nitrogen runoff, autumn-winter body condition of blue mussels Mytilus spp., natural predation and epidemic disease (avian cholera) on annual survival of adult females in ten study colonies distributed between the Netherlands and Finland. Moreover, we tested how the degree of similarity in spatial winter distributions affected the degree of similarity in annual survival among colonies. 3. None of the covariates universally affected female survival. While the quality of blue mussels in the wintering area explained almost 40 % of the variation in survival of eiders breeding on Christiansø in the south-western Baltic Sea, incidence of epidemic disease explained > 60 % in two affected colonies. Furthermore, the spatial winter distribution did not appreciably influence annual survival rates in these ten colonies. 4. The lack of universal effects of spatial winter distribution and winter conditions on survival suggests that local breeding conditions may be more important, and hence prime targets for conservation efforts. Better monitoring of e.g. food quality, predation pressure and epidemic disease at the time of breeding could be the key to better understand the population dynamics in this endangered flyway population.